Neurological disorders and imaging physics. - El-Baz, Ayman S.; Suri, Jasjit S. (IOP ebooks. 2020 collection., 2020)
This book focuses on major trends and challenges in the area of dyslexia, epilepsy and Parkinson's, and aims to identify new techniques and their applications in biomedical analysis. This fifth volume on neurological disorders explores topics such as real-time epilepsy prediction applied on EEG pediatric data; delineation of epileptogenic zone; behavioral and biological correlates and treatment of dyslexia; potential biomarkers of Parkinson's disease; Rett Syndrome; and automatic assessment of motor impairments for Parkinson's disease. This is an essential reference for students and researchers in medical imaging, brain imaging, image processing, and neurology.